STRATEGI PENGUSAHAAN DEPORTASI DETENI DI LUAR RUMAH DETENSI IMIGRASI JAKARTA DALAM MENDUKUNG PENEGAKAN HUKUM KEIMIGRASIAN - Yusuf Fadhilah Ihkrom; M. Alvi Syahrin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Deportation is one of the Immigration Administrative Actions aimed at removing foreign nationals from the territory of Indonesia due to non-compliance with immigration regulations. In practice, deportation is not always carried out for detainees accommodated within Immigration Detention Centers (Rumah Detensi Imigrasi), but may also involve detainees located outside detention facilities based on specific considerations, including limited detention capacity, operational efficiency, and administrative policies of the Directorate General of Immigration. This condition requires an effective strategy to ensure that deportation procedures are conducted in accordance with the principles of legal certainty, national security, and respect for human rights. This study aims to analyze the strategy for managing the deportation of detainees outside the Jakarta Immigration Detention Center in supporting immigration law enforcement and to identify factors affecting its effectiveness. This research employs normative legal research using statutory, conceptual, and case approaches. Legal materials were collected through library research consisting of legislation, scholarly literature, academic journals, and official documents related to immigration and deportation. The findings indicate that deportation management outside the detention center represents an adaptive policy to improve the effectiveness of immigration administrative enforcement. However, its implementation still faces several challenges, including inter-agency coordination, travel document completion, deportation funding, and the absence of comprehensive technical regulations governing deportation procedures outside detention facilities. Therefore, strengthening legal regulations, enhancing institutional coordination, and establishing clear operational standards are essential to ensure that deportation processes are carried out effectively, efficiently, and in accordance with the principles of legal certainty.